Lanthanide transport in stabilized zirconias: Interrelation between ionic radius and diffusion coefficient - Kilo, Martin (2004)
The diffusion of all stable lanthanides in calcia stabilized zirconia (CSZ) and in yttria stabilized zirconia (YSZ) was measured. Lanthanide migration enthalpies were calculated using the Mott-littleton approach. The results suggest that the bulk diffusion coefficient depends on the ionic radius of the lanthanide tracer. It was also found that the experimental activation enthalpies are about 6eV for CSZ and between 4 and 5 eV for YSZ and almost constant for all lanthanides.